Penataan Ruang pada Masyarakat Baduy - R. Cecep Eka Permana (Antropologi Indonesia, 1997)
This article describes the spaces order among the Baduy people of Southwest Java. The Baduys, who deliberately isolating themselves from influence of modernization, divides their settlement into Inner Baduy and Outer Baduy. The Inner Baduy is perceived more sacred as the ancestor spirits (karuhun) live in this area. Their stilt-house is built with north-south direction. North direction was regarded as the entrance to their settlement, while south direction perceived as sacred place. This space order is applied to all activities such a ritual, rice planting, funeral, etc.